2013
DOI: 10.1089/hgtb.2013.046
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Adeno-Associated Virus Producer Cell Lines for Research and Preclinical Vector Production

Abstract: Adeno-associated virus (AAV) producer cell lines represent an effective method for large-scale production of AAV vectors. We set out to evaluate and characterize the use of an abbreviated protocol to generate "masterwells" (MWs; a nonclonal cell population) as a platform for research and preclinical vector production. In this system, a single plasmid containing three components, the vector sequence, the AAV rep, and cap genes, and a selectable marker gene is stably transfected into HeLaS3 cells. Producer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 80 publications
0
90
0
Order By: Relevance
“…22 Recently, an AAV production system based on stable HeLa cell lines was presented that harbors the rep and cap genes and the ITR-flanked rAAV genome. 23 Considerable collateral packaging of rep and cap was reported, up to 0.62% and 0.25%, respectively, of vector genome-containing capsids. In rAAV2 vector lots for a clinical trial, the reported percentage of packaged cap genes ranged between 0.016% and 0.021%.…”
Section: Avoiding Potential Packaging Signals In Helper Gene Constructsmentioning
confidence: 99%
“…22 Recently, an AAV production system based on stable HeLa cell lines was presented that harbors the rep and cap genes and the ITR-flanked rAAV genome. 23 Considerable collateral packaging of rep and cap was reported, up to 0.62% and 0.25%, respectively, of vector genome-containing capsids. In rAAV2 vector lots for a clinical trial, the reported percentage of packaged cap genes ranged between 0.016% and 0.021%.…”
Section: Avoiding Potential Packaging Signals In Helper Gene Constructsmentioning
confidence: 99%
“…7 Encouraging preliminary results are moving rAAV gene therapy closer to a routine clinical application. Although there have been continuous and significant progressions toward flexible and scalable rAAV production in recent years, [8][9][10][11][12][13] a high demand still exists for more efficient vector production. This is partially due to the overwhelming amount of quality vectors needed to support preclinical research using large animal models and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, a disadvantage of this process is the time needed to generate and characterize producer cell lines (PCLs), which can be shortened using non-clonal ''masterwells'' (MWs). 18,26 This study generated and characterized MWs producing AAVrh8R serotype vectors harboring 5.1 and 5.4 kb genomes encoding human FVIII (hFVIII). The data demonstrate the feasibility of the PCL method to produce slightly oversized rAAV vectors.…”
Section: Gene Therapy Using Recombinant Aav (Raav)mentioning
confidence: 99%
“…The AAV2 cap in pAF-SEAP-AAV2 26 was changed to AAVrh8R to gener-ate pTP-SEAP-caprh8R. The ITRs flanking the SEAP expression cassette were removed and replaced with a blunt-ended PvuI and SapI fragment containing the 5.1 kb FVIII vector genome from pITR-mTTR202-hFVIIIco-spA to generate pTP-FVIII-5.1-caprh8R.…”
Section: Generation and Characterization Of Producer Cell Linesmentioning
confidence: 99%